If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3t = 6t + -20 Reorder the terms: 7 + -3t = -20 + 6t Solving 7 + -3t = -20 + 6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6t' to each side of the equation. 7 + -3t + -6t = -20 + 6t + -6t Combine like terms: -3t + -6t = -9t 7 + -9t = -20 + 6t + -6t Combine like terms: 6t + -6t = 0 7 + -9t = -20 + 0 7 + -9t = -20 Add '-7' to each side of the equation. 7 + -7 + -9t = -20 + -7 Combine like terms: 7 + -7 = 0 0 + -9t = -20 + -7 -9t = -20 + -7 Combine like terms: -20 + -7 = -27 -9t = -27 Divide each side by '-9'. t = 3 Simplifying t = 3
| 54x^3+2y^3= | | 5n-1=3n+7 | | 2x+23= | | 10p-11=-2+4 | | 18x^4y+24x^3y^2-10x^2y^3=0 | | 8p+10=3p-5 | | 5y^2-35=0 | | -6(x+7)+9=-7-7x | | -5+9y+4-6y= | | 2244=12x+16y | | (3x+20)(5x-50)= | | -x-(8x+1)= | | 36x^4y+15x^3y^2-9x^2y^3=0 | | (4x+10)(3x-5)= | | 12x+16y=88 | | (2y+28)(4y+26)= | | 30x^4y+39x^3y^2-9x^2y^3=0 | | t/30=12/72 | | x^4-x^2=n | | (2x-20)(6x-32)= | | 16x^4y+32x^3y^2-20x^2y^3=0 | | (3y-8)(y-12)= | | 12a^2+6a-5=0 | | 2+2*2=2 | | (y-12)(6x-32)(3y-8)(2x-20)= | | 5x-(3x-7)= | | 8c^2+22cd+9d^2=0 | | 105x^4+60x^3-30x^6= | | 6*x^4-2*x^2=n | | -13a+6-9a+12a= | | 6c^2+7cd-5d^2=0 | | (75)(5x-2)= |